Pre-columbian archeological textiles: A source of pseudomonas aeruginosa with virulence attributes - Rajkowska, Katarzyna (2020)
Pseudomonas aeruginosa is an opportunistic pathogen associated with a broad spectrum of infections in humans. However, the pathogenicity of environmental P. aeruginosa strains, especially isolates from museums and conservation laboratories, is not widely recognized. In this study, the virulence attributes of P. aeruginosa isolated from pre-Columbian textiles were compared to those of a clinical strain. Both genetically identified environmental strains (KP842564 and KP842565) exhibited a high ability to form biofilms on abiotic surfaces and high hemolytic activity. In addition, strain KP842564 was a moderate pyocyanin producer and showed proteolytic properties toward bovine serum albumin, fibrinogen, mucin, and casein. In contrast to the clinical isolate, the environmental strainswere susceptible to all the tested antimicrobial agents. The strains also showed high bioadhesion and colonization capacity on archeological textile samples, in which wool fibers were the only source of nutrients, as confirmed by scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM-EDX) analysis. This study highlights the need to identify microorganisms which inhabit historic objects, in order to avoid exposure to occupational hazards. Although the strain KP842565 exhibited only some of the examined virulence-related features, given that the production of pyocyanin and hemolysins as well as the formation of biofilm are important virulence factors of P. aeruginosa, the results indicate that these strains may present a potential health risk for humans.